2017
DOI: 10.1002/pen.24745
|View full text |Cite
|
Sign up to set email alerts
|

Effect of electron beam irradiation on dielectric properties, morphology and melt rheology of linear low density polyethylene/silicone rubber‐based thermoplastic elastomer nanocomposites

Abstract: In this study, thermoplastic elastomer nanocomposites based on linear low density polyethylene (LLDPE)/silicone rubber (SR; 90:10) filled with a 2 vol% boron nitride (BN) nanofiller were exposed to electron beam (EB) irradiation at low irradiation doses (20, 40, 50, and 100 kGy). The response of the LLDPE/SR/BN nanocomposites to the EB irradiation crosslinking was examined and compared with the non‐irradiated samples in terms of dielectric properties (permittivity and loss tangent), dielectric breakdown streng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…Both studies reported on various thermal and electrical characteristics as well as mechanical performance of the TPE blends. Recently, Hidayah et al evaluated the applicability of inorganic nanofillers in LLDPE/SR blends and effect of electron beam irradiation on the electrical insulation performance of the TPE nanocomposites.…”
Section: The Emergence Of Thermoplastic Elastomer In Electrical Insulmentioning
confidence: 99%
“…Both studies reported on various thermal and electrical characteristics as well as mechanical performance of the TPE blends. Recently, Hidayah et al evaluated the applicability of inorganic nanofillers in LLDPE/SR blends and effect of electron beam irradiation on the electrical insulation performance of the TPE nanocomposites.…”
Section: The Emergence Of Thermoplastic Elastomer In Electrical Insulmentioning
confidence: 99%
“…This high change in the dielectric constant value over lower frequencies may be because of the effect of interface polarization. With the increase in frequency, this effect of interface polarization is gradually diminished and results in less decrement of dielectric constant value . It has been mentioned earlier that the dielectric constant value is increasing with the increase in nanosilica loading within the polymer matrix when considering any particular frequency.…”
Section: Resultsmentioning
confidence: 93%
“…With the increase in frequency, this effect of interface polarization is gradually diminished and results in less decrement of dielectric constant value. 25 It has been mentioned earlier that the dielectric constant value is increasing with the increase in nanosilica loading within the polymer matrix when considering any particular frequency. This increment in dielectric constant value is because of the presence of a polar silanol group on the surface of nanosilica.…”
Section: Morphological Analysis Of Nanocomposites Through Hrtem and F...mentioning
confidence: 94%
“…It is observed that the values of dielectric constant for the nanocomposites irradiated by a 75 kGy dose are higher than blank (nanocomposite film without electron beam irradiation) as a result of the increase in the number of charges accumulated. This is due to the electron beam irradiation making the crosslinking (cross‐scission) and then producing the radicals [26].…”
Section: Resultsmentioning
confidence: 99%